1868 Colo. Sess. Laws 229 - (:unkn) unknown (My University, 1867)
§ 149: Prohibited the concealed carrying of any pistol, Bowie knife, dagger, or other deadly weapon within any city, town, or village in the territory. Punishable by fine of $5-35. Exempted sheriffs, constables, and police officers when performing their official duties.
Keywords: CARRY - CONCEALED